Technical and economic assessment of fixed, single and dual-axis tracking PV panels in low latitude countries - Bahrami, Arian; Okoye, Chiemeka Onyeka; Atikol, Ugur (Pergamon-Elsevier Science Ltd, 2017)
This study aims to contribute towards developing a sustainable roadmap for electrification program via solar energy deployment in 21 low latitude countries (0-15 degrees N) with limited access to the grid. Firstly, the available electrical energy from fixed, single and dual-axis solar tracking PV panels is demonstrated using a case study of nine selected locations in Nigeria. The annual electrical energy for the locations from a fixed 1-kW PV panel tilted at an optimal angle ranges from 1485 to 2024 kWh, with the use of seven different single and dual-axis trackers; the yield would vary between 1521 and 2611 kWh. This amount of energy output, if fully harnessed, would contribute significantly to alleviating the chronic energy shortage in Nigeria. Finally, the performance of the solar trackers in terms of the energy gain and levelized cost of electricity (LCOE) is ranked to show the most preferred option for implementation. The presented ranking patterns can be used as a valuable guide by researchers and designers in the selection of the appropriate solar trackers for 21 low latitude countries located in three continents such as those around the Gulf of Guinea in Africa, the Gulf of Thailand in Asia, and the Caribbean Sea in America. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Solar radiation; Optimum tilt angle; PV system; Tracking system; Performance ranking